Implementation of Shallot Pest Trap Model Based on Color Spectrum Using Photovoltaic Energy - Muhammad Hasan Basri; Sulistiyanto Sulistiyanto; Muhammad Imaduddin (Jurnal Penelitian Pendidikan IPA, 2023)
East Java is the second center for shallot production in Indonesia, mainly in Probolinggo Regency. Where farmers always complain about shallot crop pests such as leafminer flies, moths, and urethral pests, which will threaten the decrease in shallot production. This study aims to implement a pest-trapping model and determine the effect of the color spectrum on light intensity levels. LED lights on the interest of flying pests of shallot plants, and knowing the effective time of turning on light traps in the shallot rice fields using photovoltaic. The results of this implementation research are pest traps designed with simple and affordable tools for farmers. The color spectrum of LED lights that catch a lot of pests is the LED with the ultraviolet spectrum with the brightest light intensity, then the most effective time to turn on the light trap for onion plant pest traps is 18.00-20.00, where the electrical energy in the pest trap uses photovoltaic.